Hubungan Social Support dengan Tingkat Depresi pada Lansia - Surya, Alfonsia Yuningsi; Febryanto, Dwi; Pambudi, Hubertus Agung (JURNAL KESEHATAN PRIMER, 2024)
Introductions: Elderly individuals are those aged ≥ 60 years. The elderly is highly susceptible to health issues, including depression. Depression in the elderly is caused by various factors, including a lack of social support. Social support is the care provided by reliable and loving individuals to ensure that recipients feel emotionally supported. Fulfillment of the social support received by an elderly person will improve both their physical and mental health. This study aims to determine the relationship between social support and the level of depression in the elderly. Method: This study is quantitative research with a cross-sectional approach. The sampling technique used was cluster sampling, with a total of 84 elderly individuals selected and designated as respondents based on inclusion criteria. Chi square is used to see the relationship between variables. The measurement tools used were the Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire to measure social support and the Geriatric Depression Scale-15 (GDS-15) questionnaire to measure the level of depression, which was analyzed using Fisher's exact test. Result: The respondents who received low social support were 61.9%, while those who received high social support were 38.1%. The percentage of respondents who did not experience depression was 53.6%, and those who experienced depression were 46.4%. The Fisher's test resulted in a p-value of 0.001 < 0.05.